Las flores del mal - Baudelaire, Charles, 1821-1867; López Castellón, Enrique; Baudelaire, Charles, 1821-1867. (Tres Cantos, Madrid : Akal, 2017)
With subjects ranging from travel to drugs, sex to faith, sleep to contemplation, Baudelaire finds new beauty in the most sinister and corrupt of situations. Six poems were banned, in a conviction that was not overturned until 1949.
Online resource; title from ePub title page (Digitalia, viewed July 27, 2019)
Keywords: Electronic books